Psychotherapy Dropout: Using the Adolescent Psychotherapy Q-Set to Explore the Early In-Session Process of Short-Term Psychodynamic Psychotherapy - Fredum, Hanne Gotaas; Rost, Felicitas; Ulberg, Randi; Midgley, Nick; Thorén, Agneta; Aker, Julie Fredrikke Dalen; Johansen, Hanna Fam; Sandvand, Lena; Tosterud, Lina; Dahl, Hanne-Sofie Johnsen (Frontiers in Psychology, 2021)
Research suggests that short-term psychodynamic psychotherapy is an effective treatment for depression in adolescence, yet treatment dropout is a major concern and the understanding of what leads to dropout is poorly understood. Whilst studies have begun to explore the role of patient and therapist variables, there is a dearth of research on the actual therapy process and investigation of the interaction structures between patient and therapist. This study aims to address this paucity through the utilization of the Adolescent Psychotherapy Q-set (APQ) to examine the early treatment period. The sample includes 69 adolescents aged 16-18 years with major depressive disorder receiving short-term psychodynamic psychotherapy (STPP) as part of the First Experimental Study of Transference Work–in Teenagers (FEST-IT) trial. Of these, 21 were identified as dropouts and were compared to completers on pre-treatment patient characteristics, symptomatology, functioning, and working alliance. APQ ratings available for an early session from 16 of these drop out cases were analysed to explore the patient-therapist interaction structure. Results from the Q factor analysis revealed three distinct interaction structures that explained 54.3% of the total variance. The first described a process of mutual trust and collaboration, the second was characterised by patient resistance and emotional detachment, the third by a mismatch and incongruence between therapist and adolescent. Comparison between the three revealed interesting differences which taken together provide further evidence that the reasons why adolescents drop out of therapy vary and are multidimensional in nature.